PERTUNJUKAN LIVE MUSIC, CUSTOMER EXPERIENCE, CAFE ATMOSPHERE TERHADAP CUSTOMER SATISFACTION DI CAFE PLAYGO KOTA SIDOARJO - Tamara Asmara; , IGN Anom Maruta; Awin Mulyati (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
At this time the F&B business is growing as can be seen from the mushrooming of cafes or coffee shops throughout Indonesia. Over time, to attract cafe customers, not only selling coffee was accompanied by various innovations. As in Sidoarjo, there are lots of cafes lined up. One of them that is of concern is Cafe Playgo. This cafe is always full of visitors and there is a home band live music every day. The purpose of this study was to determine the effect of Live Music Performances, Customer Experience, and Cafe Atmosphere on the satisfaction of cafe visitors who are crowded with visitors. As for supporting this research, the method used by the author is quantitative research and with data collection techniques using questionnaires. The results showed that the live music performance variable had a positive effect on customer satisfaction, the customer experience variable had a positive effect on customer satisfaction, and the cafe atmosphere had a positive effect on customer satisfaction. To achieve maximum customer satisfaction, business people need to improve and develop what customers should need, one of which is the existence of facilities such as live music, paying attention to customer experience, and a cafe atmosphere.